Decifrando a função de processos ecológicos e evolutivos na distribuição local e regional de artrópodes em plantas - Gonçalves-Souza, Thiago [UNESP] (2012)
An understanding of how the degree of phylogenetic relatedness influences the ecological similarity among species is crucial for inferring the mechanisms governing the assembly of species. As closely related species often share similar morphological traits, both phylogeny and ecology can explain the convergence or divergence of species morphology. We evaluated the relative importance of spiders’ phylogeny and ecological niche to the variation in spider body size and shape by comparing spiders (i) between bromeliads and dicot plants and (ii) among bromeliads with distinct architectural features. We tested whether bromeliad-living spiders have similar morphological traits to spiders from surrounding dicots and whether the differences in spider body size and shape are related to bromeliad architecture or to the spiders’ phylogeny. Spiders from bromeliads were larger and flatter than spiders associated with the surrounding dicots; this pattern was explained only by the spiders’ phylogeny. However, spider flatness was related to both phylogeny and ecological niche, suggesting that both historical processes and recent adaptations drive the evolution of spider body shape. Bromeliads appear to favour larger and flatter spiders because they provide a larger resource supply and their leaves are tightly interlocked compared to surrounding dicot plants, providing shelters from predators. By partitioning the phylogenetic and ecological components of phenotypic variation, we were able to disentangle the evolutionary history of distinct spider traits and show that plant architecture plays a role in the evolution of spider body size and shape